Implementasi Pelayanan Yesus Dalam Injil Matius Kepada Penyandang Disabilitas - Yusuf Setiawan Sudarso Kusumo; Paulus Sentot Purwoko (Jurnal Apokalupsis, 2022)
The purpose of this research is to find out how big the level of implementation of Christ' ministry to people with physical disabilities based on the Gospel of Matthew among the officials of the Voice of the Bible Church (GSKI) throughout DKI Jakarta. Then to find out the dimensions and categories of the dominant background in determining Jesus' ministry to the community. persons with disabilities. The research method used is a quantitative research design with a survey method by distributing questionnaires. The results showed that the level of implementation of Jesus' ministry to the physically disabled community was in the moderate category, the most dominant dimension was teaching ministry, and the most dominant background was education. With these results, recommendations need to be improved, by seeking these officials to become faith educators who prioritize teaching Christian values ​​to persons with disabilities so that their lives are restored mentally and in character. Another strategy undertaken is to participate in programs organized by the Ecumenical Theological College in the form of the "Joint Learning Movement" and the "Service Practices in Special Schools for Handling Disabilities" and create a guidebook on how to provide effective teaching services to persons with disabilities.